The potential of citric acid production using pineapple waste - Lee, Ting Hun; Mat, Hanapi (1997)
Citric acid fermentation with Aspergillus niger ATCC 10577 in stirred tank reactors (5l) were carried out using pineapple solid and liquid waste. Highest yield (13.07g/l) was obtained with the solid pineapple waste while liquid pineapple waste obtained a 6.59 g/l yield based on the sugar consumed. Shake flasks culture were done initially to find the suitable pH and dilution rate.